Four-week unstructured break improved athletic performance in collegiate rugby players - Jensen, C. D.; Gleason, D.; VanNess, J. M. (The Journal of Strength and Conditioning Research, 2018)
This study analyzed the changes in athletic performance and anthropometric characteristics in collegiate male club rugby athletes (n = 14) after a 4-week winter break. All measurements were collected before and after the break. Body composition was assessed by body mass index and hydrostatic weighing. Performance measurements were as follows: VO2max, vertical jump, 10-yard sprint, squat max, and bench press max. Before testing, each subject was acclimated to the protocols to reduce learning effects. During the 4-week break, no workouts were provided for the athletes; it was unsupervised and unstructured. Participants were required to maintain and submit self-reported nutritional and activity logs during this period. After the break, the athletes demonstrated a 5.0% improvement in VO2max (absolute increase of 2.25 ml/kg/min), 6.8% improvement in vertical jump (1.50 inches), and a 14.3% increase in squat max (38.64 lb). Although increases in body mass (1.0%) were not significant, the body fat percentage exhibited a relative increase of 19.3% (absolute change from 13.35 to 15.93%). A significant discriminate function analysis indicated statistical differences between groups based on these variables. Self-reported behavior logs confirmed participation in >3 days of moderate to intense physical activity per week but somewhat poor dietary habits. These results indicate that collegiate rugby athletes may not need prescribed exercise routines during seasonal breaks in the athletic schedule. However, it may be beneficial to provide structured nutritional advice during unsupervised periods.